How do general practitioners recognize the definition of multimorbidity? A European qualitative study. (2nd July 2016) - Le Reste, Jean Yves; Nabbe, Patrice; Lazic, Djurdjica; Assenova, Radost; Lingner, Heidrun; Czachowski, Slawomir; Argyriadou, Stella; Sowinska, Agnieszka; Lygidakis, Charilaos; Doerr, Christa; Claveria, Ana; Le Floch, Bernard; et al.
Abstract: Background: Multimorbidity is a challenging concept for general practice. An EGPRN working group has published a comprehensive definition of the concept of multimorbidity. As multimorbidity could be a way to explore complexity in general practice, it was of importance to explore whether European general practitioners (GPs) recognize this concept and whether they would change it. Objectives: To investigate whether European GPs recognize the EGPRN concept of multimorbidity and whether they would change it. Methods: Focus group meetings and semi-structured interviews as data collection techniques with a purposive sample of practicing GPs from every country. Data collection continued until saturation was reached in every country. The analysis was undertaken using a grounded theory based method. In each national team, four independent researchers, working blind and pooling data, carried out the analysis. To ensure the internationalization of the data, an international team of 10 researchers pooled the axial and selective coding of all national teams to check the concept and highlight emerging themes. Results: The maximal variation and saturation of the sample were reached in all countries with 211 selected GPs. The EGPRN definition was recognized in all countries. Two additional ideas emerged, the use of Wonca's core competencies of general practice, and the dynamics of the doctor–patient relationship for detecting and managing multimorbidity and patient's complexity. Conclusion: European GPs recognized and enhanced the EGPRN concept of multimorbidity. These results open new perspectives regarding the management of complexity using the concept of multimorbidity in general practice.